Effect of energy losses during an impact event on the dynamic flow stress - Hamouda, A.M.S. (2002)
Determination of stress-strain properties of material and formulation of suitable constitutive laws is very important on the study of: (i) the elastic-plastic response and collapse mode of structures can be analysed for improving subsequent design, and (ii) high speed metal cutting and metal forming processes may be analysed for better estimation of the process parameters and better understanding of material flow behaviour. This paper is devoted to establish the energy losses in an existing ballistic rig. The effect of energy losses due to impact into the study of dynamic flow stress of a material is examined. Results assuming loss of kinetic energy varying from 1 to 20% of the initial energy are presented and discussed for En-9 steel. The effects of friction, inertia, and temperature rise during the dynamic compression tests are also presented and discussed. © 2002 Published by Elsevier Science B.V.